GABAergic Signaling during Spinal Cord Stimulation Reduces Cardiac Arrhythmias in a Porcine Model. (1st February 2023) - Howard-Quijano, Kimberly; Kuwabara, Yuki; Yamaguchi, Tomoki; Roman, Kenny; Salavatian, Siamak; Taylor, Bradley; Mahajan, Aman
Abstract : Background: Neuraxial modulation, including spinal cord stimulation, reduces cardiac sympathoexcitation and ventricular arrhythmogenesis. There is an incomplete understanding of the molecular mechanisms through which spinal cord stimulation modulates cardiospinal neural pathways. The authors hypothesize that spinal cord stimulation reduces myocardial ischemia–reperfusion—induced sympathetic excitation and ventricular arrhythmias through γ-aminobutyric acid (GABA)–mediated pathways in the thoracic spinal cord. Methods: Yorkshire pigs were randomized to control (n = 11), ischemia–reperfusion (n = 16), ischemia–reperfusion plus spinal cord stimulation (n = 17), ischemia–reperfusion plus spinal cord stimulation plus γ-aminobutyric acid type A (GABAA ) or γ-aminobutyric acid type B (GABAB ) receptor antagonist (GABAA, n = 8; GABAB, n = 8), and ischemia–reperfusion plus GABA transaminase inhibitor (GABAculine, n = 8). A four-pole spinal cord stimulation lead was placed epidurally (T1 to T4). GABA modulating pharmacologic agents were administered intrathecally. Spinal cord stimulation at 50 Hz was applied 30 min before ischemia. A 56-electrode epicardial mesh was used for high-resolution electrophysiologic recordings, including activation recovery intervals and ventricular arrhythmia scores. Immunohistochemistry and Western blots were performed to measure GABA receptor expression in the thoracic spinal cord. Results: Cardiac ischemia led to myocardial sympathoexcitation with reduction in activation recovery interval (mean ± SD, –42 ± 11%), which was attenuated by spinal cord stimulation (–21 ± 17%, P = 0.001). GABAA and GABAB receptor antagonists abolished spinal cord stimulation attenuation of sympathoexcitation (GABAA, –9.7 ± 9.7%, P = 0.043 vs. ischemia–reperfusion plus spinal cord stimulation; GABAB, –13 ± 14%, P = 0.012 vs. ischemia–reperfusion plus spinal cord stimulation), while GABAculine alone caused a therapeutic effect similar to spinal cord stimulation (–4.1 ± 3.7%, P = 0.038 vs. ischemia–reperfusion). The ventricular arrhythmia score supported these findings. Spinal cord stimulation during ischemia–reperfusion increased GABAA receptor expression with no change in GABAB receptor expression. Conclusions: Thoracic spinal cord stimulation reduces ischemia–reperfusion—induced sympathoexcitation and ventricular arrhythmias through activation of GABA signaling pathways. These data support the hypothesis that spinal cord stimulation–induced release of GABA activates inhibitory interneurons to decrease primary afferent signaling from superficial dorsal horn to sympathetic output neurons in the intermediolateral nucleus. Abstract : This study of Yorkshire pigs found that spinal cord stimulation reduces myocardial ischemia–reperfusion—induced myocardial sympathetic excitation and ventricular arrhythmias through γ-aminobutyric acid–mediated pathways in the thoracic spinal cord.